Effect of Different Incubation Time on Goat's Milk Dadih on Thorny Bamboo (Bambusa stenostachya Hackel) (Jurnal Ilmu dan Teknologi Hasil Ternak, 2022)
The purpose of this study was to determine the quality of dadih with bamboo in Taiwan, namely Thorny bamboo (Bambusa stenostachya Hackel) with different incubation times. The materials used are bamboo tubes, banana leaves and Alpine goat's milk from the National Pingtung University of Science and Technology (NPUST) Taiwan. Dadih is made by pasteurizing goat's milk at a temperature of 65oC for 30 minutes, allowed to stand until a temperature of 30oC, the milk is poured into a bamboo tube and covered with banana leaves, then fermented in an incubator at 37oC with time variations (0, 24, 30, 36, 42, and 48 hours). The results showed that the difference in incubation time significantly (p<0.05) on pH, total acidity, syneresis, and general characteristics of dadih. The conclusion of this study is 24-hours incubation is the best time to make dadih because the taste is similar to dadih in West Sumatra.